2016
DOI: 10.1111/andr.12210
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive investigation of sperm DNA damage and oxidative stress injury in infertile patients with subclinical, normozoospermic, and astheno/oligozoospermic clinical varicocoele

Abstract: SUMMARYOne of the main pathogeneses of varicocoele and infertility is oxidative stress (OS), nevertheless, the oxidative damaged DNA in infertile patients with varicocoele remains poorly clarified. The objective of this study was to comprehensively investigate whether sperm DNA damage and OS injury were related with different issues of varicocoele. According to the varicocoele practice guidelines, surgical treatment was not indicated in the infertile patients with subclinical (SubVc, n = 15) and normozoospermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 62 publications
(64 reference statements)
10
44
0
2
Order By: Relevance
“…Among the infertile group, patients with varicocele showed significantly higher DFI than did those without varicocele. This finding is in agreement with previous studies (Moazzam, Sharma, & Agarwal, ; Ni et al, ; Talebi, Moein, Tabibnejad, & Ghasemzadeh, ).…”
Section: Discussionsupporting
confidence: 94%
“…Among the infertile group, patients with varicocele showed significantly higher DFI than did those without varicocele. This finding is in agreement with previous studies (Moazzam, Sharma, & Agarwal, ; Ni et al, ; Talebi, Moein, Tabibnejad, & Ghasemzadeh, ).…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies demonstrated that heat-related oxidative stress or protamine deficiency in varicocele condition prone spermatozoa to DNA fragmentation (Bahreinian et al, 2015;Ni et al, 2016). In this study, we observed a significant reduction in percentage of residual histone in varicocelized rats that received Vit B+Vit E compared with varicocelized rats that received water at 4 months.…”
Section: As Shown Insupporting
confidence: 56%
“…In general, amongst the infertile groups, infertile patients with varicocele have a higher proportion of sperm with damaged DNA [27,34]. A recent study by Gual-Frau et al [27] showed that the integrity of sperm DNA in grade-I varicocele men can be improved by certain forms of oral multivitamin/antioxidant therapy, including vitamin B 12 .…”
Section: Effect Of Vitamin B12 On Sperm Parametersmentioning
confidence: 99%